Advances in Mead Aroma Research: A Comprehensive Bibliometric Review and Insights into Key Factors and Trends - Reitenbach, Amanda; Lorenzi, Adriana; Ghesti, Grace; Santos, Paula; Rodrigues, Igor; Barbosa, Ananda; Sant’Ana, Rodrigo; Fritzen-Freire, Carlise; Nowruzi, Bahareh; Burin, Vívian (Fermentation (Basel), 2025)
This article examines the key factors influencing the aromatic profile of mead, which is increasingly popular in artisanal markets worldwide. Based on a bibliometric review of 44 scientific studies, the analysis highlights the significant role of honey type in shaping mead’s sensory characteristics. Acacia honey contributes subtle floral notes, while eucalyptus honey brings bolder, resinous aromas. The bibliometric analysis also emphasizes fermentation conditions, such as temperature and yeast selection, as crucial factors. Lower fermentation temperatures help preserve volatile compounds, enhancing fruity and floral aromas, while higher temperatures lead to increased concentrations of undesirable higher alcohols. Additionally, aging mead in oak barrels for 6 to 12 months adds complexity by introducing vanilla, coconut, and spice notes from the wood’s phenolic compounds. The maturation process, including its duration and storage conditions, also enables the flavors to blend and develop over time. Moreover, the addition of herbs and fruits during fermentation or maturation has been proven to introduce new layers of aroma and flavor, with ingredients like citrus, berries, and aromatic herbs enhancing the final product with fresh, lively notes. The potential of non-Saccharomyces yeasts is also explored as an alternative for enriching aromatic profiles, with the capacity to introduce unique sensory characteristics, including diverse flavor profiles and regional or terroir-based variations. Finally, the bibliometric review reinforces the importance of selecting appropriate ingredients and controlling fermentation processes to improve mead quality. It also suggests exploring microbiomes, exotic honey varieties, and the use of herbs and fruits for even more distinct aromatic profiles.